2013
DOI: 10.1002/cbin.10188
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods for the isolation of mesenchymal stem cells from umbilical cord matrix: Proliferation and multilineage differentiation as compared to mesenchymal stem cells from umbilical cord blood and bone marrow

Abstract: We have identified the most appropriate method of isolating human umbilical cord matrix-derived mesenchymal stem cells (UCM-MSCs) and compared morphological, phenotypic, proliferative, and differentiation characteristics of UCM-MSCs with bone marrow-derived MSCs (BM-MSCs) and umbilical cord blood-derived MSCs (UCB-MSCs). Three explant culture methods and 3 enzymatic methods were compared with regards to time for primary culture, cell number, cell morphology, immune phenotype, and differentiation potential. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 36 publications
6
55
0
Order By: Relevance
“…Thus, BM-MSCs transplantation is a safe way for DFU, and intramuscular transplantation has been proved to have the best efficacy [22]. However, the number and differentiated potential of BM-MSCs decline with aging [52]. …”
Section: Bm-mscs and Dfumentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, BM-MSCs transplantation is a safe way for DFU, and intramuscular transplantation has been proved to have the best efficacy [22]. However, the number and differentiated potential of BM-MSCs decline with aging [52]. …”
Section: Bm-mscs and Dfumentioning
confidence: 99%
“…UCB-MSCs have a similar morphology, cell surface antigens, and the potential of differentiation into BM-MSCs and umbilical cord-derived mesenchymal stem cells (UC-MSCs) [42, 52, 68]. Additionally, UCB-MSCs have several advantages, such as short doubling time [69], long viable time, and anti-inflammatory activity [42].…”
Section: Umbilical Cord Blood-derived Mesenchymal Stem Cells (Ucb-mentioning
confidence: 99%
See 1 more Smart Citation
“…The primary obstacle associated with autologous chondrocyte implantation in articular cartilage repair is the loss of the chondrocyte phenotype (Duan et al, 2015). Prior work has demonstrated that MSCs can be isolated from various types of adult mesenchymal tissue, including bone marrow, skeletal muscle, adipose tissue, and human umbilical cord (Campagnoli et al, 2001;Zuk et al, 2002;Da Silva Meirelles et al, 2006;Kestendjieva et al, 2008;Hua et al, 2013). This is largely due to their high expansion efficiency and their capacity to differentiate into multiple cell types, including adipocytes, osteoblasts, chondrocytes, skeletal myocytes, and tenocytes (Pittenger et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, the frequency of MSCs is low, and only a third of CB cells provide a source for generation of MSCs in vitro. Alternative approaches for isolation of MSCs have been developed from the CT [24]. In fact some CB banks now routinely store both CB and CT, offering a unique and potentially advantageous source of HSCs, HPCs and MSCs from a single matched source.…”
Section: Cb and Ct As A Source For Mscsmentioning
confidence: 99%